2013
DOI: 10.15288/jsad.2013.74.271
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Independent Major Depressions, Alcohol Use, and Other Substance Use and Related Problems Over 30 Years in 397 Families

Abstract: ABSTRACT. Objective: Although heavy drinking is related to sadness on multiple levels, the link between alcohol use disorders (AUDs) and major depressive episodes (MDEs) is more controversial. One complicating factor is that some MDEs are temporary and only occur in the context of heavy drinking, whereas other MDEs are longer lasting and occur independently of intense alcohol intake (i.e., independent depressive episodes [IDEs]). We hypothesized that a longitudinal study that uses validated interviews with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
(73 reference statements)
1
24
1
3
Order By: Relevance
“…On the one hand, among undergraduate students, heavy drinking may lead to MDD. Indeed, alcohol is a depressant, and it has been shown that in some people depression can be induced by heavy alcohol use (Schuckit et al, 2013). Moreover, students who consume more alcohol and engage in more frequent heavy drinking are at higher risk for experiencing alcohol-related consequences (e.g., academic or relationship difficulties) that may lead to MDD.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, among undergraduate students, heavy drinking may lead to MDD. Indeed, alcohol is a depressant, and it has been shown that in some people depression can be induced by heavy alcohol use (Schuckit et al, 2013). Moreover, students who consume more alcohol and engage in more frequent heavy drinking are at higher risk for experiencing alcohol-related consequences (e.g., academic or relationship difficulties) that may lead to MDD.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this distinction, Schuckit et al (2013) conducted a 30-year follow-up of young adults to track the development and course of major depression and AUD. They found a significantly elevated association between depression and AUD among those reporting temporal proximity between their depressive episodes and bouts of heavy drinking (about 30% of all depressive episodes) but no significant elevation for AUD among those whose depressive episodes were not temporally proximal to heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha observado que en el caso de los TUS por cocaína, opiáceos o en policonsumidores el episodio de DM suele ocurrir con mayor frecuencia de forma independiente del consumo (Torrens, Gilchrist, y Domingo-Salvany, 2011) mientras que en el caso del alcohol se ha descrito una mayor prevalencia de asociación con DM inducida (Schuckit, Smith, y Kalmijn, 2013). Sin embargo se pueden encontrar ambos tipos de depresiones (primarias e inducidas) en el mismo paciente (Langås, Malt, y Opjordsmoen, 2013; To-el tratamiento.…”
Section: Características Clínicas De La Depresión Dualunclassified